Influência da adubação orgânica na qualidade da água destinada à irrigação de hortaliças - Célico, Amanda Schimidt [UNESP] (2015)
Compost from carcasses, as well as animal and vegetable waste, constitutes a viable alternative for the partial or total substitution of mineral fertilizers. However, little is known about the environmental impact of using this agricultural compound on the quality of water. The aim was to evaluate the water quality of a stream that irrigates an agricultural area treated with organic compost produced by carcasses, animal and vegetable waste. We sampled water biannually in 2013 and 2014 from six different locations: one water catchment site for vegetable irrigation, two sites upstream, two downstream from that point and one water well. The variables analyzed were pH, temperature, dissolved oxygen, conductivity, turbidity, redox potential, dissolved solids, chemical oxygen demand, chloride, nitrate, nitrite, ammonia nitrogen, total and reactive phosphorus, total coliforms, E. coli and substrate consumption (Ecoplate). The analytical results compared with national water quality standards indicated that the environment was not negatively impacted by the compost. Using the substrate consumption technique, we observed that there was no correlation between the use of the organic compost and changes in microbial populations of the different points sampled. This study showed that the use of this organic compost does not negatively influence the quality of surface water in area studied. Therefore, the organic compost is a novel and attractive alternative for local agricultural production